A glass fiber sizing agent for a prepreg reinforced polyethylene resin, a method for preparing the same, a glass fiber, and an application thereof

CN123003163APending Publication Date: 2026-10-30JUSHI GRP CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611227367.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的在于针对现有的玻璃纤维浸润剂主要针对热固性树脂或聚丙烯体系设计,因而导致其与PE树脂相容性差的问题,提供一种预浸带增强聚乙烯树脂用玻璃纤维浸润剂及其制备方法和应用,通过组分设计及其协同作用,在玻璃纤维表面构建与聚乙烯树脂具有强亲和力的界面层,显著提升复合材料的界面结合强度、耐老化性能及工艺稳定性

Benefits of technology

(1)本发明的玻璃纤维用浸润剂中,采用乙烯基三乙氧基硅烷、乙烯基三(2-甲氧基乙氧基)硅烷、氨基乙烯基双官能硅烷复配作为硅烷偶联剂,三元协同作用,既能保证其与玻璃纤维表面的良好键合,又提供与聚乙烯树脂发生接枝反应的活性位点,从而显著提高GF/PE的界面结合强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1786599617903-000001
    Figure REF-OBJ-1786599617903-000001
  • Figure REF-OBJ-1786599617903-000002
    Figure REF-OBJ-1786599617903-000002
Patent Text Reader

Abstract

The present application relates to the technical field of glass fiber production and manufacturing, and aims to solve the problem of poor compatibility between the existing glass fiber sizing agent and PE resin, and provides a glass fiber sizing agent for pre-impregnated tape reinforced polyethylene resin, a preparation method thereof, glass fiber and application thereof, wherein the silane coupling agent solid content accounts for 0.4-4% of the total mass, the film forming agent solid content accounts for 4-16% of the total mass, the lubricant solid content accounts for 0.1-3% of the total mass, the pH regulator solid content accounts for 0.05-0.5% of the total mass, and the balance is water; wherein the film forming agent is a mixture composed of maleic anhydride grafted polyethylene wax emulsion and polyvinyl alcohol emulsion, and the film forming agent solid content accounts for 4.1-15.5% of the total mass of the glass fiber sizing agent. An interface layer with strong affinity to polyethylene resin is constructed on the surface of the glass fiber, which significantly improves the interface bonding strength, aging resistance and process stability of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass fiber production and manufacturing technology, and more specifically, to a glass fiber impregnating agent for prepreg-reinforced polyethylene resin, its preparation method, glass fiber, and its applications. Background Technology

[0002] With the deepening of global energy structure transformation and sustainable development strategies, especially against the backdrop of my country's explicit goal of "carbon peaking and carbon neutrality," lightweight transportation, represented by new energy vehicles, and energy equipment upgrading, represented by the efficient development of oil and gas resources, have become important engines for promoting high-quality development of the manufacturing industry. Glass fiber (GF) reinforced polyethylene (PE) prepreg tape, due to its excellent toughness, chemical corrosion resistance, recyclability, and superior cost-effectiveness, shows broad application prospects in these two strategic areas. Lightweight components for new energy vehicles place high impact resistance and high fatigue resistance requirements on GF / PE prepreg tape, while RTP pipelines for oil and gas transportation place high pressure resistance and high creep resistance requirements on its long-term reliability. Both factors point to a fundamental improvement in the interfacial bonding strength of GF / PE.

[0003] Existing glass fiber sizing agents are mainly designed for thermosetting resins or polypropylene systems. When applied to GF / PE prepreg tapes, poor compatibility between the sizing agent and PE resin leads to insufficient interfacial bonding strength between GF and PE. Therefore, there is an urgent need for a targeted glass fiber sizing agent specifically designed for reinforced polyethylene prepreg tapes, thereby promoting the high-end application of GF / PE prepreg tapes in lightweight transportation and energy equipment. Summary of the Invention

[0004] The purpose of this invention is to address the problem that existing glass fiber impregnating agents are mainly designed for thermosetting resins or polypropylene systems, resulting in poor compatibility with PE resin. This invention provides a glass fiber impregnating agent for prepreg-reinforced polyethylene resin, its preparation method, and its application. Through component design and synergistic effects, an interface layer with strong affinity to polyethylene resin is constructed on the glass fiber surface, significantly improving the interfacial bonding strength, aging resistance, and process stability of the composite material.

[0005] This invention is achieved through the following technical solution: This invention provides a glass fiber impregnating agent for prepreg reinforced polyethylene resin, comprising a silane coupling agent, a film-forming agent, a lubricant, a pH adjuster, and water; the silane coupling agent is a mixture of vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, and aminovinyl difunctional silane (γ-(2-vinylbenzyl)aminopropyltrimethoxysilane); the film-forming agent is a mixture composed of maleic anhydride-grafted polyethylene wax emulsion and polyvinyl alcohol emulsion.

[0006] The solid content of the wetting agent is 3.2-17.1%; and the percentage of the solid mass of each effective component to the total mass of the wetting agent is as follows: silane coupling agent 0.4-4%, film-forming agent 4-16%, lubricant 0.1-3%, pH adjuster 0.05-0.5%, and the balance is water.

[0007] Furthermore, the solid content of the wetting agent is more preferably controlled at 5.8-17.1%, and the corresponding percentage of the solid mass of each effective component to the total mass of the wetting agent is: silane coupling agent 0.5-2.8%, film-forming agent 5.3-15.5%, lubricant 0.2-1.8%, pH adjuster 0.05-0.3%, with the balance being water.

[0008] In this invention, the silane coupling agent is the core component for constructing the molecular bridge between the inorganic glass fiber and the organic polyethylene resin. The silane coupling agent molecule has a typical dual-reactive functional group structure, with the general formula YR-SiX3. The X group, such as methoxy or ethoxy groups, readily hydrolyzes in an aqueous medium to generate reactive silanol groups. These silanol groups can undergo dehydration condensation with the silanol groups on the glass fiber surface to form Si-O-Si covalent bonds, thus firmly bonding to the fiber surface. This chemical bonding process is fundamental to obtaining excellent interfacial adhesion, effectively transferring stress from the flexible resin matrix to the high-strength glass fiber under load, preventing interfacial debonding. Simultaneously, the amount of silane coupling agent must be controlled within a suitable range. If the silane coupling agent content is too low, a complete and continuous coating layer cannot be formed on the large specific surface area of ​​the fiber, resulting in numerous unmodified blind areas on the fiber surface. These exposed areas lack reactive sites for the film-forming agent and subsequent polyethylene resin, becoming stress concentration points and crack initiation sites when the composite material is under stress. If the silane coupling agent content is too high, after hydrolysis, it not only reacts with the fiber surface but also undergoes condensation reactions between molecules, generating siloxane oligomers or even polymers. These self-condensation products deposit on the fiber surface, forming rigid and brittle microregions that cannot effectively transfer stress and are easily broken under stress, becoming the starting point for interfacial failure. Therefore, this invention uses vinyltriethoxysilane compounded with vinyltri(2-methoxyethoxy)silane and aminovinyl difunctional silane as a silane coupling agent, and controls its solid content ratio to be 0.4%~3.2%, preferably in the range of 0.5%~2.8%.

[0009] Preferably, in the silane coupling agent, the mass ratio of vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, and aminovinyl difunctional silane is 1:0.5~2:0.1~0.6.

[0010] To achieve synergistic regulation of hydrolysis rate and stability, the specific dosage relationships of vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, and aminovinyl difunctional silane in the silane coupling agent were defined. This is based on the following: Vinyltris(2-methoxyethoxy)silane has a faster hydrolysis rate; its silanoxy group at one end can undergo hydrolysis and condensation reactions with the silanol groups on the glass fiber surface to form strong chemical bonds, firmly anchoring it to the glass fiber surface; the vinyl group at the other end can react with polyethylene resin containing unsaturated double bonds to form initial bonds with the glass fiber surface. Vinyltriethoxysilane, on the other hand, has a relatively slower hydrolysis rate, providing a longer activity window and continuing to react during subsequent drying. The amino group in aminovinyl silane can undergo room-temperature amidation reactions with maleic anhydride in the film-forming agent, pre-constructing interfacial covalent bridges and significantly improving interfacial adhesion at room temperature; amino silane can buffer the thermal expansion difference between glass fiber and PE, reducing interfacial microcracks under high and low temperature cycling. By using the above-mentioned ternary compound silane coupling agent, the hydrolysis rate gradient is matched, avoiding local self-polymerization and more uniform coating on the fiber surface. It can also avoid the problems of the coupling agent itself condensing and deactivating due to excessively fast hydrolysis, or insufficient treatment due to excessively slow hydrolysis. Thus, a uniform and dense coating of silane on the fiber surface is achieved, optimizing the bonding efficiency with glass fiber.

[0011] Although polyethylene is an inert, non-polar resin and difficult to form strong covalent bonds directly with vinyl groups, this invention utilizes the bridging effect of subsequent film-forming agents, particularly maleic anhydride-grafted polyethylene wax, to make vinyl groups a key anchor point. During high-temperature processing, under the influence of initiator residue or mechanical force, vinyl groups can undergo grafting or entanglement reactions with maleic anhydride groups or PE segments on the grafted polyethylene wax molecular chain. The ternary silane compound is used to form a flexible interface layer with a suitable crosslinking density on the fiber surface, effectively transferring stress and buffering internal stress caused by the difference in thermal expansion coefficients between the resin and the fiber.

[0012] Preferably, in the film-forming agent, the grafting rate of the maleic anhydride-grafted polyethylene wax emulsion ranges from 0.8% to 3%, and the molecular weight is from 2000 to 9000; the degree of alcoholysis of the polyvinyl alcohol is from 87% to 99%, and the molecular weight is from 20000 to 60000.

[0013] Furthermore, in the film-forming agent, the mass ratio of maleic anhydride-grafted polyethylene wax emulsion to polyvinyl alcohol emulsion is 1:1~3.

[0014] Film-forming agents are used in large quantities in glass fiber impregnation, and their performance significantly impacts the overall effect of the impregnation, directly affecting the glass fiber manufacturing process and the final composite material's performance. The main function of the film-forming agent is to aggregate glass fiber monofilaments into bundles; therefore, the type and amount of film-forming agent determine the fiber bundle structure. The film-forming agent must possess good bonding ability to protect the glass fibers, ensuring smooth subsequent processing and meeting the mechanical property requirements of the composite product.

[0015] In this invention, the film-forming agent is a compound of maleic anhydride-grafted polyethylene wax emulsion and polyvinyl alcohol. The maleic anhydride-grafted polyethylene wax emulsion, due to its molecular structure containing both polyethylene wax segments compatible with polyethylene resin and reactive maleic anhydride polar groups, can form a dual effect of chemical bonding and physical entanglement between glass fiber and polyethylene resin, significantly improving the interfacial bonding strength between glass fiber and polyethylene resin, thereby enhancing the mechanical properties and creep resistance of the composite material product.

[0016] The compounded film-forming agent forms a stable interfacial network structure on the glass fiber surface through the synergistic effect of chemical reaction and physical entanglement. Maleic anhydride-grafted polyethylene wax molecular chains contain highly reactive maleic anhydride groups; while polyvinyl alcohol molecular chains contain a large number of hydroxyl groups. In the aqueous impregnating agent system, the maleic anhydride groups can partially hydrolyze to generate carboxyl groups, which undergo esterification and crosslinking reactions with the hydroxyl groups of polyvinyl alcohol, forming chemical bonds. Simultaneously, unreacted hydroxyl and carboxyl groups can form hydrogen bonds, further enhancing intermolecular bonding. Through chemical crosslinking and physical entanglement, the two form a semi-interpenetrating polymer network structure with a certain crosslinking density on the fiber surface. This ensures both the strength and toughness of the interfacial layer and organically combines the polyethylene segments in the maleic anhydride-grafted polyethylene wax that are compatible with PE resin with the film-forming protective properties of polyvinyl alcohol, achieving excellent coating of the glass fiber and interfacial reinforcement of the polyethylene resin.

[0017] Furthermore, insufficient film-forming agent prevents the formation of a continuous and complete protective film on the glass fiber surface, resulting in poor fiber bundle cohesion due to ineffective bonding between the fiber filaments. This leads to a large amount of fuzz and broken filaments during use, severely impacting production efficiency and product quality. Excessive film-forming agent leads to an excessively high viscosity of the sizing agent system, making it difficult to spread evenly on the fiber surface during high-speed drawing. This easily results in localized accumulation or uneven coating, forming defect points. These defect points become stress concentration areas in the composite material, inducing early failure.

[0018] Preferably, the lubricant is a compound composed of polyethylene glycol and stearate, wherein the relative molecular mass of polyethylene glycol is 400-1000 and the mass ratio of polyethylene glycol to stearate is 1:0.3-1.

[0019] Polyethylene glycol, as a water-soluble polymer lubricant, has ether bonds in its molecular chain that can form hydrogen bonds with water molecules, creating a hydrophilic lubricating film on the fiber surface. This reduces the coefficient of friction between the fiber and the contact parts during the drawing process. It also has certain hygroscopic and antistatic properties, effectively suppressing fuzz formation. Stearate, as an oil-based lubricant, has a long-chain alkyl structure that endows it with excellent hydrophobicity and polar adsorption capacity. It can preferentially adsorb onto the glass fiber surface and the interface of the contact parts, forming a strong molecular lubricating layer that maintains a stable lubrication effect under high-temperature and high-speed drawing conditions.

[0020] This invention employs a compound lubricant consisting of an aqueous phase and an oil phase. Polyethylene glycol provides excellent water solubility and spreadability, ensuring uniform distribution of the sizing agent on the fiber surface, while stearate enhances the durability and extreme pressure lubrication of the lubricating film. Together, they form a hydrophilic-hydrophobic dual composite lubricating layer on the fiber surface, meeting the high-temperature, high-speed lubrication requirements during yarn drawing and providing continuous protection during fiber drying and subsequent textile processing. This avoids problems such as moisture absorption and re-dampening or lubricating film rupture caused by a single lubricant, significantly reducing hairiness and ensuring the continuity and stability of the glass fiber direct yarn in the prepreg tape preparation process. Since an excessively high lubricant ratio can affect the interfacial bonding between the glass fiber and resin, reducing impregnation and thus impacting mechanical properties, the mass ratio of polyethylene glycol to stearate is controlled at 1:0.3~1 in this invention.

[0021] Preferably, the pH value of the glass fiber impregnating agent material system of the present invention is controlled at 3.5~4.5, and the pH value adjuster used is one or more of glacial acetic acid, citric acid, etc. Acetic acid and citric acid, as organic weak acids, can provide a stable acidic buffer environment and have no metal ion residue, so they have no adverse effects on the fiber and subsequent processing.

[0022] This invention adjusts the pH of the sizing agent system to a suitable acidic range to catalyze the hydrolysis reaction of vinyltriethoxysilane and vinyltris(2-methoxyethoxy)silane. Under acidic conditions, the alkoxy groups of the silane coupling agent hydrolyze to generate highly reactive silanol groups, laying the foundation for subsequent condensation bonding with silanol groups on the glass fiber surface. Simultaneously, the suitable pH conditions inhibit premature self-condensation of the hydrolyzed silanol groups, ensuring that the coupling agent acts on the fiber surface in an active state.

[0023] When the pH value is too high, the coupling agent hydrolyzes slowly and incompletely, resulting in insufficient formation of silanol groups, which cannot form a sufficient number of chemical bonds with the glass fiber, thus reducing the interfacial bonding strength. When the pH value is too low, the coupling agent hydrolyzes too quickly, easily undergoing intermolecular self-condensation reaction to form siloxane oligomers, losing its bonding activity with the fiber surface. Furthermore, an excessively acidic environment may damage the fiber strength and affect the stability of other components in the sizing agent.

[0024] The present invention also provides a method for preparing the above-mentioned glass fiber impregnating agent for prepreg reinforced polyethylene resin, specifically including the following steps: S1 First, add water accounting for 20-40% of the total mass of the impregnating agent to the container, then add a pH adjuster to control the pH value of the glass fiber impregnating agent at 3.5-4.5; then add a silane coupling agent, stir until completely dissolved, and let stand for 10-30 minutes to obtain a silane active liquid.

[0025] S2 Take another film-forming agent and dilute it with water at 2-4 times its mass to obtain a diluted film-forming agent solution; then add the diluted film-forming agent solution to the silane active solution that has been stirred evenly in S1 and stir evenly.

[0026] S3 Take another lubricant and dilute it with 2-5 times its weight of water to obtain a lubricant dilution; then add the lubricant dilution to the mixture in S2 after stirring evenly, and stir evenly.

[0027] S4. Add water to the mixture obtained in S3 until the sizing agent mass setting value is reached, stir evenly, filter through a 100-mesh filter, and let stand for 30-50 minutes to obtain the glass fiber sizing agent for prepreg reinforced polyethylene resin.

[0028] The water used is all deionized water at room temperature of 15-30℃.

[0029] The glass fiber sizing agent for prepreg-reinforced polyethylene resin provided by this invention is applied to glass fiber monofilaments via direct yarn processing to form glass fibers. This glass fiber sizing agent can be used in direct yarn processing of glass fibers and is suitable for prepreg tape processes in polyethylene resin systems. The polyethylene composite material reinforced with this agent exhibits high impact resistance and high pressure resistance.

[0030] Preferably, the combustible content in the glass fiber coated with the sizing agent is controlled at 0.5-1.8%, more preferably at 0.5-1.5%. The combustible content refers to the percentage of the amount of sizing agent coated on the glass fiber relative to the mass of the glass fiber.

[0031] The glass fiber obtained by treating prepreg-reinforced polyethylene resin with a glass fiber impregnating agent in this invention can be used in prepreg-reinforced polyethylene high-strength materials.

[0032] The technical solution of the present invention has at least the following advantages and beneficial effects: (1) In the glass fiber impregnating agent of the present invention, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane and aminovinyl difunctional silane are used as silane coupling agents. The ternary synergistic effect can not only ensure good bonding with the glass fiber surface, but also provide active sites for grafting reaction with polyethylene resin, thereby significantly improving the interfacial bonding strength of GF / PE.

[0033] (2) Maleic anhydride-grafted polyethylene wax emulsion and polyvinyl alcohol are used as film-forming agents. Maleic anhydride-grafted polyethylene wax has excellent compatibility with polyethylene matrix, and its anhydride groups can form chemical bonds with coupling agents. Polyvinyl alcohol provides good film-forming and bundle-forming properties, protecting fibers from damage during processing. Combining these two can achieve excellent interfacial bonding and a balance of processing performance.

[0034] (3) Using a blend of polyethylene glycol and stearate as a lubricant ensures the smoothness of the fiber while avoiding the negative impact of a single lubricant on the interface bonding, which is beneficial for the rapid impregnation and uniform molding of the prepreg tape.

[0035] (4) Using a pH adjuster to control the pH value of the sizing agent system between 3.5 and 4.5 can significantly promote the hydrolysis rate of vinyltriethoxysilane and vinyltri(2-methoxyethoxy)silane and inhibit their premature polycondensation, ensuring that the coupling agent acts on the fiber surface in the best active state.

[0036] In summary, this invention, through component design and synergistic effects, constructs an interface layer with strong affinity for polyethylene resin on the surface of glass fiber, significantly improving the interfacial bonding strength, aging resistance, and process stability of the composite material. It provides a glass fiber treatment agent technology that is more suitable for the application of reinforced polyethylene prepreg tape, promoting the high-end application of GF / PE prepreg tape in the fields of transportation lightweighting and energy equipment, and has important technical value and industrial significance. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, they are performed according to conventional conditions or conditions recommended by the manufacturer; where the manufacturers of the instruments, equipment, reagents, or raw materials used are not specified, they are all conventional products that can be purchased commercially.

[0038] Examples 1-9

[0039] The composition of the glass fiber impregnating agent for prepreg-reinforced polyethylene resin proposed in this invention is as follows: ①Silane coupling agents: vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, γ-(2-vinylbenzyl)aminopropyltrimethoxysilane; ② Maleic anhydride grafted polyethylene wax emulsion: grafting rate range 1.8%, molecular weight 5000; ③ Polyvinyl alcohol: degree of alcoholysis is 88%, molecular weight is 22000.

[0040] ④ Lubricant: PEG600, polyethylene glycol 400 monostearate (PEG400MS) ⑤ pH adjuster: glacial acetic acid.

[0041] Glass fiber impregnating agents were prepared according to the specific dosages of each component in Table 1 as Examples 1-9, denoted as M1-M9: Table 1. Composition and dosage of glass fiber impregnating agent in Examples 1-9

[0042] The percentages of the components in Table 1 are all percentages of the solid content of each component relative to the solid mass of the wetting agent.

[0043] Using the above-mentioned raw material components, a glass fiber impregnating agent is prepared according to the following process: First, add water (30% of the total mass of the sizing agent) to the container, then add a pH adjuster to control the pH of the glass fiber sizing agent at 4.0 ± 0.1. Next, add a silane coupling agent, stir until completely dissolved, and let stand for 20 minutes to obtain a silane active liquid. Separately, take a film-forming agent and dilute it with water to three times its mass to obtain a diluted film-forming agent solution. Then add the diluted film-forming agent solution to the silane active liquid and stir evenly to obtain mixture a. Separately, take a lubricant and dilute it with water to three and a half times its mass to obtain a diluted lubricant solution. Then add the diluted lubricant solution to mixture a and stir evenly. Finally, add water to the set mass of the sizing agent, stir evenly, filter through a 100-mesh filter, and let stand for 35 minutes to obtain the glass fiber sizing agent for prepreg reinforced polyethylene resin. Comparative Example 1 This comparative example is basically the same as Example 1, except that the silane coupling agent is a single component vinyltriethoxysilane, and the total solid content of the silane coupling agent remains unchanged.

[0044] Comparative Example 2 This comparative example is basically the same as Example 1, except that the silane coupling agent is a single component vinyltris(2-methoxyethoxy)silane, and the total solid content of the silane coupling agent remains unchanged.

[0045] Comparative Example 3 This comparative example is basically the same as Example 1, except that the silane coupling agent is a single-component aminovinyl difunctional silane, and the total solid content of the silane coupling agent remains unchanged.

[0046] Comparative Example 4 This comparative example is basically the same as Example 1, except that the film-forming agent is a single-component polyvinyl alcohol and does not contain maleic anhydride-grafted polyethylene wax emulsion.

[0047] Comparative Example 5 The wetting agent in this comparative example specifically includes the following components: Coupling agent: γ-aminopropyltriethoxysilane, 2.0%; Film-forming agent a: polyurethane emulsion, 4.0%; Film-forming agent b: Polyvinyl alcohol, 2.0%; Lubricant: Polyethylene glycol + stearate, 0.8%; Antistatic agent: Dodecyltrimethylammonium chloride, 0.4%; pH adjuster: glacial acetic acid, 0.1%.

[0048] Comparative Example 6 The wetting agent in this comparative example specifically includes the following components: Coupling agent: γ-aminopropyltriethoxysilane, 2.0%; Film-forming agent a: Polypropylene wax emulsion, 4.0%; Film-forming agent b: Polyethylene wax emulsion, 1.5%; Film-forming agent c: polyurethane emulsion, 0.5%; Lubricant: 0.8% PEG600 + PEG400MS (mass ratio 1:1); Antistatic agent: Dodecyltrimethylammonium chloride; pH adjuster: glacial acetic acid, 0.1%.

[0049] Test case The sizing agents used in Examples 1-9 and Comparative Examples 1-6 were applied to glass fiber production. The glass fiber was produced using an alkali-free glass fiber tank furnace drawing production line, with a glass fiber linear density of 1000 tex. The composite material was prepared using a prepreg process, with a glass fiber content of 60%, a production speed of 10 m / min, and polyethylene resin (SKJM720) as the reinforcing resin. The compatibilizer component was 4% (POLYRAM BONDYRAM® 1001). Finally, test strips or samples were molded for evaluation, and the performance of the composite material was tested and comprehensively evaluated according to the evaluation methods described below.

[0050] The performance testing and evaluation methods for glass fiber reinforced copolymer polypropylene resin composites are as follows: (1) Tensile strength and modulus: according to ASTM D3039 test standard; (2) Bending strength and modulus: according to ISO 178 test standard; (3) Impact strength: according to ISO 179 Charpy test standard.

[0051] The test results for the above samples are shown in Table 2 below: Table 2 Performance test results of different samples

[0052] As can be seen from the test results of the sample strips in Table 2, the mechanical properties of the glass fiber reinforced polyethylene resin samples coated with the glass fiber sizing agent of the present invention in Examples 1-9 are significantly improved compared with those using the sizing agents of Comparative Examples 1-6, and the amount of hairiness is significantly reduced. This indicates that the sizing agent of the present invention can effectively improve the GF / PE interface bonding and has good process protection performance.

[0053] In summary, the glass fiber roving treated with the sizing agent described in this invention can effectively improve the interfacial bonding strength between glass fiber and polyethylene resin, resulting in composite material products with excellent mechanical properties. This meets market and application demands.

[0054] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A glass fiber impregnating agent for prepreg-reinforced polyethylene resin, characterized in that, It includes a silane coupling agent, a film-forming agent, a lubricant, a pH adjuster, and water, and the solid content of the glass fiber impregnating agent is 3.2% to 17.1%. The film-forming agent is a mixture of maleic anhydride-grafted polyethylene wax emulsion and polyvinyl alcohol emulsion, and the solid content of the film-forming agent accounts for 4.1 to 15.5% of the total mass of the glass fiber impregnating agent.

2. The glass fiber impregnating agent for prepreg-reinforced polyethylene resin according to claim 1, characterized in that, The glass fiber impregnating agent comprises, by mass percentage, 0.4-4% solid content of silane coupling agent, 4-16% solid content of film-forming agent, 0.1-3% solid content of lubricant, 0.05-0.5% solid content of pH adjuster, and the remainder is water.

3. The glass fiber impregnating agent for prepreg-reinforced polyethylene resin according to claim 1, characterized in that, The silane coupling agent is a mixture of vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, and aminovinyl difunctional silane, wherein the mass ratio of vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, and aminovinyl difunctional silane is 1:0.5~2:0.1~0.

6.

4. The glass fiber impregnating agent for prepreg-reinforced polyethylene resin according to claim 1, characterized in that, In the film-forming agent, the mass ratio of maleic anhydride-grafted polyethylene wax emulsion to polyvinyl alcohol emulsion is 1:1~3, and the grafting rate of maleic anhydride-grafted polyethylene wax emulsion ranges from 0.8 to 3%.

5. The glass fiber impregnating agent for prepreg-reinforced polyethylene resin according to claim 1, characterized in that, The lubricant is a compound composed of polyethylene glycol and stearate, with the polyethylene glycol having a relative molecular mass of 400-1000 and the mass ratio of polyethylene glycol to stearate being 1:0.3-1.

6. The glass fiber impregnating agent for prepreg reinforced polyethylene resin according to claim 1, characterized in that, pH adjusters are one or more of glacial acetic acid, citric acid, etc.

7. A method for preparing a glass fiber impregnating agent for prepreg-reinforced polyethylene resin according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1 First, add water accounting for 20-40% of the total mass of the impregnating agent to the container, then add a pH adjuster to control the pH value of the glass fiber impregnating agent at 3.5-4.5; then add a silane coupling agent and stir until completely dissolved to obtain a silane active liquid. S2 Take another film-forming agent and dilute it with water at 2-4 times its mass to obtain a diluted film-forming agent solution; then add the diluted film-forming agent solution to the silane active solution that has been stirred evenly in S1 and stir evenly. S3 Take another lubricant and dilute it with 2-5 times its weight of water to obtain a lubricant dilution; then add the lubricant dilution to the mixture in S2 after stirring evenly, and stir evenly. S4. Add water to the mixture obtained in S3 until the sizing agent mass setting value is reached, stir evenly, filter, and let stand to obtain the glass fiber sizing agent for prepreg reinforced polyethylene resin.

8. A type of glass fiber, characterized in that, It is produced by coating the prepreg tape reinforced polyethylene resin with glass fiber sizing agent according to any one of claims 1 to 6.

9. The application of the glass fiber as described in claim 8 in a prepreg-reinforced polyethylene high-strength material.